1993
DOI: 10.1111/j.1365-2761.1993.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and lenticular lesions in vitamin‐C‐deficient juvenile red drum, Sciaenops ocellatus (L.)

Abstract: OcuUw pathologic findings in eyes of ascorbic acid-deficienl juvenile red drum. Sciaenops ocellatus (L.), are described. Abnormalities in the most severely affected eyes ineluded: reduced globe size and lack of normal globe rigidity; vascular congestion and intraocular haemorrhage; lenticular lesions whieh included disorganization of posterior eortex. vacuolation of posterior subcapsular cortex and posterior migration of lens epithelium; and severe central retinal degeneration. The authors suspect that retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…1 (C)). The eye abnormalities caused by vitamin C deficiency were previously reported in fish species, such as rainbow trout (Halver et al 1975), red drum (Collins et al 1993), and oscar (Fracalossi et al 1998). also discussed that a high concentration of vitamin C in the fish eye reflects the importance of vitamin C in this organ and demonstrated that dietary vitamin C deficiency in cyprinid fish resulted in significant depletion of ascorbate concentrations in all eye compartments; retina, lens, and humour.…”
Section: Discussionmentioning
confidence: 75%
“…1 (C)). The eye abnormalities caused by vitamin C deficiency were previously reported in fish species, such as rainbow trout (Halver et al 1975), red drum (Collins et al 1993), and oscar (Fracalossi et al 1998). also discussed that a high concentration of vitamin C in the fish eye reflects the importance of vitamin C in this organ and demonstrated that dietary vitamin C deficiency in cyprinid fish resulted in significant depletion of ascorbate concentrations in all eye compartments; retina, lens, and humour.…”
Section: Discussionmentioning
confidence: 75%
“…Vitamin C nutrition of red drum was investigated in one study ( Collins 1990). Based on that study, retinal and lenticular lesions associated with a dietary vitamin C deficiency in red drum were characterized ( Collins et al . 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic of the sway movement was analyzed owing to the stabilogram diffusion parameters proposed by Collins & de Lucas [8]. The computation of the stabilogram diffusion function for squatting showed a very small diffusion compared to standing and it was not possible to determine the two phases brought to light in standing condition.…”
Section: Resultsmentioning
confidence: 99%